2015
DOI: 10.1155/2015/248060
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Multidrug Resistance Gene‐1 (MDR1/ABCB1) and Glutathione S‐Transferase Gene and the Risk of Inflammatory Bowel Disease among Moroccan Patients

Abstract: Inflammatory bowel diseases (IBD) are multifactorial disorders resulting from environmental and genetic factors. Polymorphisms in MDR1 and GSTs genes might explain individual differences in susceptibility to IBD. We carried out a case-control study to examine the association of MDR1 (C1236T and C3435T), GSTT1, and GSTM1 polymorphisms with the risk of IBD. Subjects were genotyped using PCR-RFLP for MDR1 gene and multiplex PCR for GSTT1 and GSTM1. Meta-analysis was performed to test the association of variant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…2.5.2.18) are belongs to a family of multifunctional enzymes which conjugate electrophilic intermediates with the endogenous tripeptide glutathione (GSH) [1]. GSTs are ubiquitous, multitalented enzymes which catalyse the nucleophilic addition of the glutathione (Glu-Cys-Gly) to numerous hazardous xenobiotic including phase I electrophilic and carcinogenic metabolites [2]. There are cytosolic, mitochondrial and membrane associated GSTs, but detoxification is the key function of cytosolic GSTs [1].…”
Section: Introductionmentioning
confidence: 99%
“…2.5.2.18) are belongs to a family of multifunctional enzymes which conjugate electrophilic intermediates with the endogenous tripeptide glutathione (GSH) [1]. GSTs are ubiquitous, multitalented enzymes which catalyse the nucleophilic addition of the glutathione (Glu-Cys-Gly) to numerous hazardous xenobiotic including phase I electrophilic and carcinogenic metabolites [2]. There are cytosolic, mitochondrial and membrane associated GSTs, but detoxification is the key function of cytosolic GSTs [1].…”
Section: Introductionmentioning
confidence: 99%
“…GSTs are widely distributed in nature and are present in both prokaryotes and eukaryotes as the principal Phase II detoxifying enzymes [2]. They constitute a superfamily of ubiquitous, multifunctional enzymes (GSTs; EC 2.5.1.18) which catalyze the nucleophilic addition of the tripeptide glutathione (GSH; g-Glu-Cys-Gly) to several hazardous xenobiotics, including phase I electrophilic and carcinogenic metabolites [3][4][5] thereby, neutralizing their electrophilic sites and rendering the products more water-soluble and facilitating their elimination from the cell by Phase III enzymes [6]. In addition, GSTs can serve as peroxidases, isomerases and thiol transferases [7].…”
Section: Introductionmentioning
confidence: 99%
“…There were five publications that assessed the association of the GSTT1 null genotype with CD and five publications for UC. Thus, we extracted 10 individual studies [17-21]. As a result, 16 individual studies from 11 publications were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Ernst et al reported the GSTT1 null genotype was not associated with UC or CD [19]. Previous studies also reported conflicting findings on the association between the GSTT1 null genotype and IBD [18, 21-24]. Therefore, we conducted a meta-analysis of observational studies to evaluate the association.…”
Section: Introductionmentioning
confidence: 99%